Low-cost mine filling material and preparation method thereof

By using a variety of industrial solid waste such as red mud, acidic excitants, fly ash, coal gangue, basalt fiber waste wire and waste molecular sieve-based self-repairing materials, the problem of high cost in the prior art of red mud filling materials is solved, and the preparation of mine filling materials with low cost, high strength and high toughness is achieved.

CN119683923APending Publication Date: 2025-03-25GUIZHOU UNIV

Patent Information

Application Number
CN202411850980.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When using red mud as mine filling material, the need to add cement leads to high costs, limiting the wide application of red mud in the filling field.

Method used

A variety of industrial solid wastes such as red mud, acidic excitants, fly ash, coal gangue, basalt fiber waste silk and waste molecular sieve-based self-repair materials are used to promote the dissolution and hydration reaction of elements in red mud through acidic excitants, forming high-strength hydration products, and improving the toughness and crack resistance of the material through fibers and self-repair materials.

Benefits of technology

It realizes the low-cost preparation of high-strength, toughness and durability of mine filling materials, reduces the use of cement components, reduces production costs, and effectively utilizes industrial solid waste and reduces environmental pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190576100000101
    Figure BDA0005190576100000101
  • Figure BDA0005190576100000111
    Figure BDA0005190576100000111
  • Figure BDA0005190576100000112
    Figure BDA0005190576100000112
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste utilization, and discloses a low-cost mine filling material and a preparation method thereof. The low-cost mine filling material comprises the following raw materials in parts by mass: 100 parts of red mud, 15-25 parts of an acid activator, 4-10 parts of fly ash, 4-10 parts of coal gangue, 5-12 parts of basalt fiber waste silk, 1-8 parts of a waste molecular sieve-based self-repairing material and 70-100 parts of water. Various industrial solid wastes such as the red mud, the ardealite, the fly ash, the coal gangue, the basalt fiber waste filaments and the waste silicon-aluminum molecular sieves are adopted, so that the source of the mine filling material can be effectively expanded, the cost is low, the environmental pressure caused by waste stacking is reduced, and good economic and environmental benefits are generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste utilization, and in particular to a low-cost mine filling material and a preparation method thereof. Background Art

[0002] Red mud is a strongly alkaline solid waste that is inevitably produced during the production of alumina. About 1 to 1.5 tons of red mud are produced for every ton of alumina produced. Taking the widely used Bayer process as an example, red mud, as a by-product of the alkaline process, is extremely alkaline and has properties such as fine particle size and high heavy metal content. Large amounts of stockpiled red mud not only occupy precious land resources, but its highly alkaline chemical composition may also penetrate into the soil and groundwater systems, posing a serious threat to the surrounding environment. Therefore, exploring low-cost, environmentally friendly ways to treat and utilize red mud on a large scale has become a technical problem that needs to be solved urgently.

[0003] In recent years, researchers have been actively engaged in the research on the resource utilization of red mud solid waste, striving to transform it into a high-value resource. At present, the research focus at home and abroad is mainly on the use of red mud to produce building materials, ceramic products, adsorption materials, new functional materials, and the recovery of iron, aluminum, titanium, sodium and even rare metal elements from red mud. In the existing technology of producing building materials with red mud as raw material, most of the red mud is partially replaced with cement as a cementitious material. For example, in the Chinese patent application with publication number CN118479817A, a red mud high-dosage hazardous waste solidification filling material and its preparation method are proposed. The filling material includes solid phase components and water. The mass fractions of each component in the solid phase component are: 50-80 parts of Bayer red mud, 10-30 parts of coal slag, 20 parts of cement, 0-1 parts of water reducer, 0-0.15 parts of chelated fiber, and the mass ratio of water to solid phase components is 62:100. For another example, in the Chinese patent application with publication number CN118108476A, a red mud synergistic multi-source solid filling material and a preparation method are proposed, which includes, by weight, 50-60 parts of red mud, 10-25 parts of desulfurized ash, 15-25 parts of cement, 2-5 parts of sodium dodecyl sulfate, 2-5 parts of sodium sulfate, 2-5 parts of gypsum, 3-5 parts of cementitious material, 5-6 parts of mineral powder, 5-6 parts of activator, 2-3 parts of stimulant, 5-8 parts of accelerator, 35-45 parts of water and 0.9-1.5 parts of water reducer.

[0004] However, although the above schemes all use red mud as the main raw material, the addition of cement components cannot be avoided, which undoubtedly increases the cost from the raw material point of view and largely limits the widespread application of red mud in the field of filling for large-scale consumption. Summary of the invention

[0005] The purpose of the present invention is to provide a low-cost mine filling material and a preparation method thereof, so as to solve the problem of high cost caused by adding cement in the existing large-scale red mud disposal solution.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a low-cost mine filling material, comprising the following raw materials in parts by weight:

[0008] 100 parts of red mud, 15-25 parts of acidic activator, 4-10 parts of fly ash, 4-10 parts of coal gangue, 5-12 parts of basalt fiber waste, 1-8 parts of waste molecular sieve-based self-healing material, and 70-100 parts of water;

[0009] Wherein, the acidic activator comprises a mixture of sulfuric acid, aluminum sulfate and phosphogypsum.

[0010] Preferably, in the low-cost mine filling material, the acidic activator includes, by mass, 3 to 8 parts of sulfuric acid, 2 to 5 parts of aluminum sulfate, and 10 to 12 parts of phosphogypsum.

[0011] Preferably, in the low-cost mine filling material, the particle size of the red mud is 30-150 μm, and the moisture content is ≤5%; the particle size of the fly ash is 0.01-2 mm; and the particle size of the coal gangue is 5-35 mm.

[0012] Preferably, in the low-cost mine filling material, the length of the basalt fiber waste is 20 to 50 mm, and the aspect ratio is 30 to 60:1.

[0013] Preferably, in the low-cost mine filling material, the method for preparing the waste molecular sieve-based self-repairing material comprises the following steps:

[0014] The waste porous silicon-aluminum molecular sieve, alkali and water are mixed to perform an activation reaction; the activated product, sodium alginate and water are mixed to perform coating to obtain a waste molecular sieve-based self-healing material;

[0015] The base comprises a mixture of triethanolamine and calcium hydroxide.

[0016] Preferably, in the low-cost mine filling material, the mass ratio of the discarded porous silica-alumina molecular sieve to the alkali is 1:0.1-0.4; the mass ratio of the triethanolamine to the calcium hydroxide is 1-3:1.

[0017] Preferably, in the low-cost mine filling material, the conditions of the activation reaction include: temperature of 90 to 180° C. and time of 4 to 12 hours.

[0018] Preferably, in the low-cost mine filling material, the mass ratio of the discarded porous silica-alumina molecular sieve to the sodium alginate is 1:0.5-1; the coating conditions include: temperature of 50-80°C and time of 10-15h.

[0019] The present invention also provides a method for preparing a low-cost mine filling material, comprising the following steps:

[0020] Red mud, acidic activator, fly ash, coal gangue, basalt fiber waste, waste molecular sieve-based self-healing material and water are mixed according to the mass ratio to obtain a filling slurry;

[0021] The filling slurry is cured to obtain low-cost mine filling material.

[0022] Preferably, in the preparation method, the mixing speed is 150-300 rpm; the curing conditions include: temperature of 15-30° C., humidity ≥95%, and time ≥28 days.

[0023] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) Red mud is a low-value alkaline solid waste. The present invention uses a mixture of sulfuric acid, aluminum sulfate and phosphogypsum as an acidic activator to promote the dissolution of aluminum, iron, silicon and other elements in red mud by providing an acidic environment. The dissolved aluminum, iron and other elements are converted into corresponding sulfates, and trace phosphoric acid in phosphogypsum can form a variety of complexes with other ions in the solution. In addition, Ca in phosphogypsum 2+ Ions and Na in red mud + The ion replacement reaction promotes the dissociation of the red mud structure, and the dissociated structure and the complex are continuously condensed and cross-linked to form hydration products such as hydrated calcium silicate gel, hydrated calcium aluminate gel and silica-alumina polymer gel. These gel-like substances are interconnected to improve the strength of the filling material. At the same time, the present invention ensures that the system does not present an overly strong acidic environment by accurately controlling the amount of the acidic activator, thereby protecting the complex structure generated during the hydration process and ensuring the smooth progress of the hydration reaction.

[0025] (2) The present invention adds basalt fiber waste, which has a stable chemical structure, excellent chemical resistance and alkali resistance, can not be corroded in alkaline environment, and can be directly used as a reinforcing material in filling materials; basalt fiber waste also has high strength characteristics and good heat resistance, which effectively improves the overall strength and toughness of the filling material. At the same time, basalt fiber waste can also significantly improve the high temperature stability and low temperature crack resistance of the filling body, which is due to the fiber's good adaptability to temperature changes and its optimization effect on stress distribution. By dispersing and bearing stress, basalt fiber waste effectively reduces the temperature stress generated during the hydration reaction, as well as the stress concentration phenomenon that may occur when the filling material is bearing load; and the micro-expansion effect of the fiber helps to offset part of the volume change, further enhancing the structural stability and durability of the filling material.

[0026] (3) The present invention adds fly ash and coal gangue. The aluminum oxide and silicon dioxide in the coal gangue and fly ash work synergistically with the calcium sulfate in the phosphogypsum and the acid-activated red mud. A dense gel structure can be generated through a hydration reaction. The calcium, silicon and aluminum increasing effects of the coal gangue and fly ash are utilized to further increase the content of active calcium, active silicon and active aluminum in the hydration reaction environment, providing favorable conditions for the formation of hydrated calcium silicate and hydrated calcium aluminosilicate, thereby greatly improving the strength of the filling material. In addition, from the perspective of particle size, the coal gangue particles are larger, while the fly ash particles are smaller. The particle size grading of the above two components has a synergistic and complementary effect with the red mud. The generated hydration products can fill the internal pores and cracks to the maximum extent, which is beneficial to improve the fluidity of the filling material and ensure that its strength after coagulation and hardening meets the application requirements.

[0027] (4) The waste molecular sieve-based self-repairing material prepared by the present invention uses waste porous silicon-aluminum molecular sieves, which have the characteristics of strong adsorption capacity and porous structure, and can stimulate more active sites through alkali. These active sites can effectively consolidate and adsorb heavy metal ions, reducing the leaching of heavy metal ions in high-doped red mud-based filling materials. Sodium alginate contains a large amount of -COO-, which can show polyanionic behavior in aqueous solution and can react with Ca in alkali. 2+ The ion exchange reaction occurs to form a cross-linked network structure to obtain a hydrogel, which makes the self-healing material have water retention properties and can meet the needs of self-repair of cracks in filling materials. And through further coating with sodium alginate, heavy metal ions can be more effectively consolidated to prevent their leaching.

[0028] (5) The present invention uses a variety of industrial solid wastes such as red mud, phosphogypsum, fly ash, coal gangue, basalt fiber waste and waste silicon-aluminum molecular sieve, which can effectively expand the source of mine filling materials with low cost and reduce the environmental pressure caused by waste dumping, thus generating good economic and environmental benefits. DETAILED DESCRIPTION

[0029] The present invention provides a low-cost mine filling material, comprising the following raw materials in parts by weight:

[0030] 100 parts of red mud, 15-25 parts of acidic activator, 4-10 parts of fly ash, 4-10 parts of coal gangue, 5-12 parts of basalt fiber waste, 1-8 parts of waste molecular sieve-based self-healing material, and 70-100 parts of water;

[0031] Wherein, the acidic activator comprises a mixture of sulfuric acid, aluminum sulfate and phosphogypsum.

[0032] In the present invention, the particle size of the red mud is preferably 30 to 150 μm, more preferably 50 to 120 μm, and more preferably 60 to 80 μm; and the water content is preferably ≤5%.

[0033] In the present invention, the source and composition of the red mud are not limited and are well known in the art. When the raw material of the red mud does not meet the aforementioned particle size and moisture content, the raw material of the red mud is ground and dried in sequence to achieve the required particle size and moisture content.

[0034] In the present invention, the acidic activator includes, by mass, 3 to 8 parts of sulfuric acid, more preferably 3 to 5 parts, and more preferably 4 parts; 2 to 5 parts of aluminum sulfate, more preferably 3 to 5 parts, and more preferably 3 parts; and 10 to 12 parts of phosphogypsum, more preferably 11 to 12 parts, and more preferably 12 parts.

[0035] In the present invention, the particle size of the phosphogypsum is preferably 0.1 to 5 mm, more preferably 0.5 to 3 mm, and even more preferably 0.8 to 1 mm.

[0036] In the present invention, the source and composition of the phosphogypsum in the acidic activator are not limited and are well known in the art. When the raw material of the phosphogypsum does not meet the aforementioned particle size, the raw material of the phosphogypsum is ground to achieve the required particle size.

[0037] In the present invention, the weight percentage of the acidic activator is preferably 15 to 25 parts, more preferably 19 to 23 parts, and more preferably 19 parts.

[0038] In the present invention, the particle size of the fly ash is preferably 0.01 to 2 mm, more preferably 0.04 to 1 mm, and even more preferably 0.04 to 0.08 mm.

[0039] In the present invention, the source and composition of the fly ash are not limited and are well known in the art. When the fly ash raw material does not meet the aforementioned particle size, the fly ash raw material is ground to achieve the required particle size.

[0040] In the present invention, the mass fraction of the fly ash is preferably 4 to 10 parts, more preferably 6 to 10 parts, and more preferably 10 parts.

[0041] In the present invention, the particle size of the coal gangue is preferably 5 to 35 mm, more preferably 10 to 25 mm, and even more preferably 10 to 15 mm.

[0042] In the present invention, the source and composition of the coal gangue are not limited and are well known in the art. When the raw material of the coal gangue does not meet the aforementioned particle size, the raw material of the coal gangue is crushed to achieve the required particle size.

[0043] In the present invention, the mass fraction of the coal gangue is preferably 4 to 10 parts, more preferably 8 to 10 parts, and even more preferably 10 parts.

[0044] In the present invention, the length of the basalt fiber waste is preferably 20-50 mm, more preferably 26-42 mm, and more preferably 30-35 mm; the aspect ratio is preferably 30-60:1, more preferably 45-60:1, and more preferably 45:1.

[0045] In the present invention, the source and composition of the basalt fiber waste are not limited and are well known in the art. When the raw material of the basalt fiber waste does not meet the aforementioned length, the raw material of the basalt fiber waste is sheared to reach the required length.

[0046] In the present invention, the weight percentage of the waste basalt fibers is preferably 5 to 12 parts, more preferably 8 to 12 parts, and even more preferably 10 parts.

[0047] In the present invention, the method for preparing the waste molecular sieve-based self-repairing material comprises the following steps:

[0048] The waste porous silicon-aluminum molecular sieve, alkali and water are mixed to perform an activation reaction; the activated product, sodium alginate and water are mixed to perform coating to obtain a waste molecular sieve-based self-healing material;

[0049] The base comprises a mixture of triethanolamine and calcium hydroxide.

[0050] In the present invention, the source and composition of the waste porous silica-alumina molecular sieve are not limited and are well known in the art.

[0051] In the present invention, the mass ratio of the triethanolamine to the calcium hydroxide is preferably 1 to 3:1, more preferably 2.5 to 3:1, and more preferably 2.5:1.

[0052] In the present invention, the mass ratio of the waste porous silica-alumina molecular sieve to the base is preferably 1:0.1-0.4, more preferably 1:0.2-0.35, and more preferably 1:0.35.

[0053] In the present invention, in the activation reaction, the ratio of the mass of the waste porous silica-alumina molecular sieve to the volume of the water is preferably 1 g: 10-30 mL, more preferably 1 g: 15-25 mL, and more preferably 1 g: 20 mL.

[0054] In the present invention, the conditions for the activation reaction include: the temperature is preferably 90-180°C, more preferably 100-150°C, more preferably 150°C; the time is preferably 4-12h, more preferably 8-12h, more preferably 10h.

[0055] In the present invention, the source of the sodium alginate is not limited and is well known in the art.

[0056] In the present invention, the mass ratio of the waste porous silica-alumina molecular sieve to the sodium alginate is preferably 1:0.5-1, more preferably 1:0.6-1, and more preferably 1:0.8.

[0057] In the present invention, during the coating process, the ratio of the mass of the waste porous silica-alumina molecular sieve to the volume of water is preferably 1 g: 15-40 mL, more preferably 1 g: 15-25 mL, and even more preferably 1 g: 20 mL.

[0058] In the present invention, the coating conditions include: the temperature is preferably 50-80°C, more preferably 65-80°C, and more preferably 65°C; the time is preferably 10-15h, more preferably 12-15h, and more preferably 12h.

[0059] In the present invention, the mass fraction of the water is preferably 70 to 100 parts, more preferably 85 to 100 parts, and even more preferably 92 parts.

[0060] The present invention also provides a method for preparing a low-cost mine filling material, comprising the following steps:

[0061] Red mud, acidic activator, fly ash, coal gangue, basalt fiber waste, waste molecular sieve-based self-healing material and water are mixed according to the mass ratio to obtain a filling slurry;

[0062] The filling slurry is cured to obtain low-cost mine filling material.

[0063] In the present invention, the mixing speed is preferably 150 to 300 rpm, more preferably 180 to 250 rpm, and more preferably 200 rpm. The present invention does not limit other conditions for the mixing, as long as the obtained filling slurry is mixed uniformly.

[0064] In the present invention, the curing conditions include: the temperature is preferably 15-30°C, more preferably 20-25°C, and more preferably 25°C; the humidity is preferably ≥95%, and the time is preferably ≥28 days.

[0065] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] In Examples 1 to 3 of the present invention and Comparative Examples 1 to 4, red mud, phosphogypsum, fly ash, coal gangue, basalt fiber waste, and waste porous silicon-alumina molecular sieve are all the following components:

[0067] The composition of red mud (by mass fraction): Al2O3 28.33%, SiO2 27.88%, CaO 18.69%, Fe2O3 9.82%, Na2O 5.12%, TiO2 4.43%, K2O 2.39%, SO3 1.3%, MgO 1.2%, P2O5 0.27%;

[0068] The composition of fly ash (by mass fraction): SiO2 51.52%, Al2O3 27.93%, Fe2O3 9.63%, TiO2 2.72%, CaO 2.11%, SO3 1.75%, Na2O 1.52%, K2O 1.45%, MgO 0.837%, P2O5 0.153%, V2O5 0.0848%, ZnO 0.0556%;

[0069] The composition of coal gangue (by mass fraction): SiO2 46.74%, Al2O3 19.51%, Fe2O3 22.56%, MgO 3.49%, CaO 2.73%, other impurities 4.97%;

[0070] The composition of basalt fiber waste (by mass fraction): Al2O3 16.24%, Fe2O3 6.87%, FeO 2.81%, MgO 4.76%, CaO 6.34%, TiO2 0.97%, Na2O 6.84%, K2O 1.27%, the balance is SiO2 and unavoidable impurities;

[0071] The pore size of the discarded porous silicon-alumina molecular sieve is 50-100 nm, and the porosity is 45%.

[0072] Example 1

[0073] This embodiment provides a low-cost mine filling material, comprising the following raw materials in parts by weight:

[0074] 100 parts of red mud, 4 parts of sulfuric acid, 3 parts of aluminum sulfate, 12 parts of phosphogypsum, 10 parts of fly ash, 10 parts of coal gangue, 10 parts of basalt fiber waste, 8 parts of waste molecular sieve-based self-healing materials, and 92 parts of water;

[0075] The red mud raw material is ground and dried in sequence to obtain red mud with a particle size of 60 to 80 μm and a moisture content of ≤5%;

[0076] Grinding the phosphogypsum raw material to obtain phosphogypsum with a particle size of 0.8 to 1 mm;

[0077] Grinding the fly ash raw material to obtain fly ash with a particle size of 0.04 to 0.08 mm;

[0078] The gangue raw material is crushed to obtain gangue with a particle size of 10 to 15 mm;

[0079] The basalt fiber waste raw material is sheared to obtain basalt fiber waste with a length of 30 to 35 mm and an aspect ratio of 45:1;

[0080] The method for preparing the waste molecular sieve-based self-repairing material in Example 1 comprises the following steps:

[0081] Mix 100g of discarded porous silica-alumina molecular sieve, 25g of triethanolamine, 10g of calcium hydroxide and 2000mL of water, activate the reaction at 150°C for 10h, and then filter; mix the activated product, 80g of sodium alginate (manufacturer: Langfang Qianyao Technology Co., Ltd.) and 2000mL of water, and coat at 65°C for 12h to obtain a discarded molecular sieve-based self-healing material.

[0082] The method for preparing the low-cost mine filling material of this embodiment comprises the following steps:

[0083] According to the mass ratio, red mud, acid activator, fly ash, coal gangue, basalt fiber waste, waste molecular sieve-based self-healing material and water are mixed uniformly at a stirring speed of 200 rpm to obtain a filling slurry;

[0084] The filling slurry is cured at 25° C. and 96% humidity for 28 days to obtain a low-cost mine filling material.

[0085] Example 2

[0086] This embodiment provides a low-cost mine filling material, comprising the following raw materials in parts by weight:

[0087] 100 parts of red mud, 8 parts of sulfuric acid, 5 parts of aluminum sulfate, 10 parts of phosphogypsum, 6 parts of fly ash, 4 parts of coal gangue, 5 parts of basalt fiber waste, 3 parts of waste molecular sieve-based self-healing materials, and 85 parts of water;

[0088] The red mud raw material is ground and dried in sequence to obtain red mud with a particle size of 120 to 150 μm and a moisture content of ≤5%;

[0089] Grinding the phosphogypsum raw material to obtain phosphogypsum with a particle size of 3 to 5 mm;

[0090] Grinding the fly ash raw material to obtain fly ash with a particle size of 0.01 to 0.05 mm;

[0091] The gangue raw material is crushed to obtain gangue with a particle size of 25 to 30 mm;

[0092] The basalt fiber waste raw material is sheared to obtain basalt fiber waste with a length of 20 to 26 mm and an aspect ratio of 30:1;

[0093] The method for preparing the waste molecular sieve-based self-repairing material in Example 2 comprises the following steps:

[0094] Mix 100g of discarded porous silica-alumina molecular sieve, 5g of triethanolamine, and 5g of calcium hydroxide with 2000mL of water, activate the reaction at 180°C for 8h, and then filter; mix the activated product, 60g of sodium alginate (manufacturer: Langfang Qianyao Technology Co., Ltd.) with 2000mL of water, and coat it at 80°C for 15h to obtain a discarded molecular sieve-based self-healing material.

[0095] The preparation method of the low-cost mine filling material in Example 2 is the same as that in Example 1.

[0096] Example 3

[0097] This embodiment provides a low-cost mine filling material, comprising the following raw materials in parts by weight:

[0098] 100 parts of red mud, 5 parts of sulfuric acid, 2 parts of aluminum sulfate, 12 parts of phosphogypsum, 4 parts of fly ash, 8 parts of coal gangue, 8 parts of basalt fiber waste, 5 parts of waste molecular sieve-based self-healing materials, and 86 parts of water;

[0099] The red mud raw material is ground and dried in sequence to obtain red mud with a particle size of 30 to 50 μm and a moisture content of ≤5%;

[0100] Grinding the phosphogypsum raw material to obtain phosphogypsum with a particle size of 0.1 to 0.5 mm;

[0101] Grinding the fly ash raw material to obtain fly ash with a particle size of 1 to 2 mm;

[0102] Crushing the coal gangue raw material to obtain coal gangue with a particle size of 5 to 10 mm;

[0103] The basalt fiber waste raw material is sheared to obtain basalt fiber waste with a length of 42 to 48 mm and an aspect ratio of 60:1;

[0104] The method for preparing the waste molecular sieve-based self-repairing material in Example 3 comprises the following steps:

[0105] Mix 100g of discarded porous silica-alumina molecular sieve, 15g of triethanolamine, and 5g of calcium hydroxide with 2000mL of water, activate the reaction at 100°C for 12h, and then filter; mix the activated product, 100g of sodium alginate (manufacturer: Langfang Qianyao Technology Co., Ltd.) with 2000mL of water, and coat it at 50°C for 12h to obtain a discarded molecular sieve-based self-healing material.

[0106] The preparation method of the low-cost mine filling material in Example 3 is the same as that in Example 1.

[0107] Comparative Example 1

[0108] This comparative example provides a low-cost mine filling material and a preparation method thereof, which is different from Example 1 in that phosphogypsum is deleted, and other parameter conditions are the same as those of Example 1.

[0109] Comparative Example 2

[0110] This comparative example provides a low-cost mine filling material and a preparation method thereof, which is different from Example 1 in that fly ash and coal gangue are deleted, and other parameter conditions are the same as those in Example 1.

[0111] Comparative Example 3

[0112] This comparative example provides a low-cost mine filling material and a preparation method thereof. The difference from Example 1 is that the basalt fiber waste is deleted, and other parameter conditions are the same as those of Example 1.

[0113] Comparative Example 4

[0114] This comparative example provides a low-cost mine filling material and a preparation method thereof. The difference from Example 1 is that the discarded molecular sieve-based self-healing material is deleted, and other parameter conditions are the same as those in Example 1.

[0115] According to the national standard GB / T 1346-2011 “Test methods for water consumption, setting time and stability of cement of standard consistency”, the initial and final setting times of mine filling materials were tested. The results are shown in Table 1.

[0116] Table 1. Initial and final setting time of Examples 1 to 3 and Comparative Examples 1 to 4

[0117] sample Initial setting time / h Final setting time / h Example 1 5.7 14.5 Example 2 5.3 11.4 Example 3 6.1 13.5 Comparative Example 1 5.6 14.8 Comparative Example 2 5.2 13.9 Comparative Example 3 5.4 14.2 Comparative Example 4 4.2 10.1

[0118] It can be seen from Table 1 that deleting one or some components has little effect on the initial and final setting time, but it will cause premature setting due to the lack of self-healing materials.

[0119] According to GB / T 2419-2005 “Determination of fluidity of cement mortar”, the fluidity of the mine filling material mortar was tested. The results are shown in Table 2.

[0120] Table 2. Fluidity of Examples 1 to 3 and Comparative Examples 1 to 4

[0121]

[0122]

[0123] It can be seen from Table 2 that deleting one or some components has little effect on fluidity, but it will cause premature coagulation and reduce fluidity due to the lack of self-repairing materials; the lack of fly ash and coal gangue will weaken the complementary effect of particles of different particle sizes, thereby reducing fluidity.

[0124] The slump of mine filling materials was tested according to the national standard GB / T 50080-2016 “Standard for test methods for properties of ordinary concrete mixtures”, and the results are shown in Table 3.

[0125] Table 3. Slump of Examples 1 to 3 and Comparative Examples 1 to 4

[0126] sample Reading / mm Example 1 242 Example 2 305 Example 3 281 Comparative Example 1 336 Comparative Example 2 329 Comparative Example 3 263 Comparative Example 4 254

[0127] It can be seen from Table 3 that deleting one or some components has little effect on the slump, but the lack of phosphogypsum or fly ash and coal gangue will reduce their hydration reaction with red mud, thereby increasing the slump; the lack of self-healing materials will also lead to premature coagulation, slightly reducing the slump.

[0128] According to the national standard GB / T 17671-2021 "Test method for strength of cement mortar", the compressive strength and flexural strength of the mine filling material were tested, and the results are shown in Table 4.

[0129] Table 4. Compressive strength and flexural strength of Examples 1 to 3 and Comparative Examples 1 to 4

[0130]

[0131]

[0132] As shown in Table 4, due to the excitation effect of phosphogypsum on red mud, deleting phosphogypsum will seriously affect the overall strength and toughness of the filling material, resulting in a decrease in both compressive and flexural strengths; fly ash and coal gangue can be used as aggregates and fillers for mine filling materials. After deleting these two components, the internal structure of the filling material becomes loose, resulting in a significant decrease in compressive and flexural strengths; basalt fiber waste can significantly improve the crack resistance and toughness of mine filling materials. After deleting basalt fiber waste, the flexural strength of the filling material is greatly affected, but the compressive strength can still be maintained at a certain level due to the presence of other components; and after deleting the abandoned molecular sieve-based self-healing material, although the overall strength of the filling material has decreased, it can still maintain a certain level. Therefore, the different components of the low-cost mine filling material of the present invention can synergistically improve the compressive strength and flexural strength.

[0133] According to the national environmental protection standard HJ 557-2010 “Toxicity leaching method of solid waste – horizontal oscillation method”, the mine filling material was subjected to horizontal oscillation method to extract the leachate, and the heavy metals and elements in the leachate were analyzed. The results are shown in Table 5.

[0134] Table 5. Toxicity results of mine filling material horizontal oscillation leaching method in Examples 1 to 3 and Comparative Examples 1 to 4

[0135]

[0136]

[0137] As can be seen from Table 5, in the schemes of deleting phosphogypsum, deleting fly ash and coal gangue, deleting basalt fiber waste or deleting abandoned molecular sieve-based self-healing materials, the precipitation of heavy metal elements and other elements has different degrees of improvement, especially in Comparative Example 4, which has the highest precipitation content of heavy metal elements. This shows that the self-healing materials added in the present invention have a good effect of fixing heavy metal elements. In addition, the materials such as phosphogypsum, fly ash and coal gangue added in the present invention can form a hydration structure with excellent bonding with red mud in the system, and cooperate with the self-healing materials to reduce the precipitation of elements.

[0138] The mine filling materials prepared in Example 1 and Comparative Example 4 were prefabricated with surface cracks by applying loads, and the width of the prefabricated surface cracks was between 0.10 and 0.35 mm. The prefabricated cracked specimens were placed in a prepared alkaline solution (sodium hydroxide solution with a pH of 9) or a neutral solution (0.005 mol / L sodium chloride solution) and cured for 28 days, and then the crack repair effect was observed. The crack repair effect is characterized by the degree of impermeability repair. The initial permeability K0 of the cracked specimen before repair is set, and the permeability after curing and repair is set to K1. The impermeability recovery rate is defined as D, and is calculated according to Formula 1. The aforementioned experiment was carried out to obtain the impermeability recovery rate of the cracked specimen after 28 days of placement, and the results are shown in Table 6.

[0139] D=(K0-K1)÷K0×100%...Formula 1.

[0140] Table 6. Results of anti-permeability recovery rate

[0141]

[0142]

[0143] From the results in Table 6, it can be seen that compared with the mine filling material without adding self-repairing components, after curing for 28 days in an alkaline environment, the mine filling material with added self-repairing materials showed significantly improved anti-seepage performance. This result strongly proves that the mine filling material developed by the present invention has the ability to automatically repair cracks, and after repair, its anti-seepage performance has been significantly restored and improved. In addition, when the external environment is in alkaline conditions, the performance of the mine filling material with added self-repairing materials is superior to that in a neutral environment.

[0144] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low-cost mine filling material, characterized in that: Contains the following raw materials in parts by weight: 100 parts of red mud, 15-25 parts of acidic activator, 4-10 parts of fly ash, 4-10 parts of coal gangue, 5-12 parts of basalt fiber waste, 1-8 parts of waste molecular sieve-based self-healing material, and 70-100 parts of water; Wherein, the acidic activator comprises a mixture of sulfuric acid, aluminum sulfate and phosphogypsum.

2. A low-cost mine filling material as claimed in claim 1, characterized in that: The acidic activator includes, by weight, 3 to 8 parts of sulfuric acid, 2 to 5 parts of aluminum sulfate, and 10 to 12 parts of phosphogypsum.

3. A low-cost mine filling material as claimed in claim 1 or 2, characterized in that: The particle size of the red mud is 30-150 μm, and the moisture content is ≤5%; the particle size of the fly ash is 0.01-2 mm; and the particle size of the coal gangue is 5-35 mm.

4. A low-cost mine filling material as claimed in claim 3, characterized in that: The length of the basalt fiber waste is 20 to 50 mm, and the aspect ratio is 30 to 60:

1.

5. A low-cost mine filling material as claimed in claim 1, characterized in that: The method for preparing the waste molecular sieve-based self-repairing material comprises the following steps: The waste porous silicon-aluminum molecular sieve, alkali and water are mixed to perform an activation reaction; the activated product, sodium alginate and water are mixed to perform coating to obtain a waste molecular sieve-based self-healing material; The base comprises a mixture of triethanolamine and calcium hydroxide.

6. A low-cost mine filling material as claimed in claim 5, characterized in that: The mass ratio of the waste porous silica-alumina molecular sieve to the alkali is 1:0.1-0.4; the mass ratio of the triethanolamine to the calcium hydroxide is 1-3:

1.

7. A low-cost mine filling material as claimed in claim 5, characterized in that: The conditions of the activation reaction include: temperature of 90 to 180° C. and time of 4 to 12 hours.

8. A low-cost mine filling material as claimed in claim 6 or 7, characterized in that: The mass ratio of the waste porous silica-alumina molecular sieve to the sodium alginate is 1:0.5-1; the coating conditions include: a temperature of 50-80°C and a time of 10-15h.

9. A method for preparing a low-cost mine filling material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Red mud, acidic activator, fly ash, coal gangue, basalt fiber waste, waste molecular sieve-based self-healing material and water are mixed according to the mass ratio to obtain a filling slurry; The filling slurry is cured to obtain low-cost mine filling material.

10. The preparation method according to claim 9, characterized in that: The mixing speed is 150-300 rpm; the curing conditions include: temperature of 15-30° C., humidity ≥ 95%, and time ≥ 28 days.

Citation Information

Patent Citations

  • Red mud synergistic multi-source solid filling material and preparation method thereof

    CN118108476A

  • High-content red mud hazardous waste curing filling material and preparation method thereof

    CN118479817A

Cited By

  • Coal mine filling paste material based on sulfur-resistant curing agent and preparation method thereof

    CN120441280A

  • Coal mine filling paste material based on anti-sulfur curing agent and preparation method thereof

    CN120441280B

  • Dry-mixed thin anti-crack waterproof plastering mortar and preparation method thereof

    CN121248201A